DEVELOPMENT OF FOOD SECURITY INFORMATION SYSTEM BASED ON BUSINESS INTELLIGENCE IN FOOD SECURITY AGENCY, MINISTRY OF AGRICULTURE, INDONESIA - Hendrawaty, Manise; Harisno, Harisno (CommIT (Communication and Information Technology) Journal, 2014)
Food is the main basic need of human, because of that fulfillment of human need of food has to be fulfilled. So it can fulfill that need, then government institution, Food Security Agency (BKP) is formed so it can monitor fulfillment of food need of society. The goals of this writing are to develop food security information system that provides dashboard facility based on business intelligence, to develop food security information system that can give fast, precise and real time information about food security, to develop decision-making support system for chairman in food security institution. Data is obtained from questionnaires to 51 respondents that are chairmen in Food Security Agency. Data is analyzed with SWOT analysis method for business environment and IT balanced scorecard (IT BSC) for IS/IT environment. The result of analysis of food security information system in Food Security Agency can help chairman in decision-making by presenting information about dashboard that gives fast, precise and real time information. It can be concluded that development of information is successfully done.